Surat Kabar Merdeka dalam Arus Krisis Kebebasan Pers Pada Masa Demokrasi Terpimpin (1960-1965) - Syifa Rizky Maulani; Sri Martini, S. S, M. Hum; Dr. Kurniwati, M.Si (Program Studi Pendidikan Sejarah Fakultas Ilmu Sosial dan Hukum Universitas Negeri Jakarta, 2025)
The research entitled Merdeka Newspaper in the Current of Press Freedom Crisis During the Guided Democracy Era (1960-1965) aims to examine and describe how Merdeka newspaper adapted or faced the current of press freedom crisis during the Guided Democracy period (1960-1965) with its strategy, as well as its impact on the role of the media as a pillar of democracy. Using historical research methods and analytical descriptive approaches with authoritarian press theory and Gramsci's hegemony theory. This study shows that the Guided Democracy era was marked by restrictions on press freedom through various government policies that made the mass media a tool for state ideological propaganda. Merdeka newspaper founded by B.M. Diah experienced similar pressures but still tried to maintain its independence. By using Antonio Gramsci's Authoritarian Press and Hegemony theories, this study shows that despite facing state pressure, Merdeka still tried to carry out its journalistic function through editorial compromise. Keywords : Merdeka Newspapers, Guided Democracy, Freedom of the Press, Authoritarian Press, Hegemony.